Phlorizin Prevents Glomerular Hyperfiltration but not Hypertrophy in Diabetic Rats. (26th August 2008) - Malatiali, Slava; Francis, Issam; Barac-Nieto, Mario
Abstract : The relationships of renal and glomerular hypertrophies to development of hyperfiltration and proteinuria early in streptozotocin-induced diabetes were explored. Control, diabetic, phlorizin-treated controls, and diabetic male Fischer rats were used. Phlorizin (anNa + -glucose cotransport inhibitor) was given at a dose sufficient to normalize blood glucose. Inulin clearance (C inulin ) and protein excretion rate (PER) were measured. For morphometry, kidney sections were stained with periodic acid Schiff. At one week, diabetes PER increased 2.8-folds (P < .001 ), C inulin increased 80% (P < .01 ). Kidney wet and dry weights increased 10%–12% (P < .05 ), and glomerular tuft area increased 9.3% (P < .001 ). Phlorizin prevented proteinuria, hyperfiltration, and kidney hypertrophy, but not glomerular hypertrophy. Thus, hyperfiltration, proteinuria, and whole kidney hypertrophy were related to hyperglycemia but not to glomerular growth. Diabetic glomerular hypertrophy constitutes an early event in the progression of glomerular pathology which occurs in the absence of mesangial expansion and persists even after changes in protein excretion and GFR are reversed through glycemic control.